Another Look at Platysmaplasty in Facelifting - Fedok, Fred G. (Facial Plastic Surgery, 2020)
Over the history of facial rejuvenation surgery there has been a progressive assimilation of knowledge about the anatomy of neck structures that are central to the manifestations of the aging neck. These advances in knowledge have been accompanied by the innovation and introduction of several surgical techniques to restore the neck to a more youthful appearance. The rejuvenation of the aging neck frequently incorporates a consideration and execution of accepted methods to restore the platysma muscles to a more aesthetic form. Lasting and dependable surgical techniques remain somewhat elusive and late failures in the neck continue to be a frustration for both patients and surgeons.In this manuscript, the author reviews some of the more enduring and innovative methods to manage the platysma in facelifting and cites the rationale and limitations of the various techniques. The concept of the restoration of an effective platysma “sling” in the upper neck to eliminate platysma bands and recreate a defined jawline is highlighted. A framework of patient evaluation and decision making is presented, and a suggested individualized application of accepted surgical maneuvers is suggested.
Keywords: facelift; platysma; platysmaplasty; platysma suspension; jawline; platysma bands